THE CONTEMPORARY INTERNATIONAL TAX SYSTEM, DEVELOPING COUNTRIES, BEPS AND OTHER CURRENT ISSUES / O SISTEMA TRIBUTÁRIO INTERNACIONAL CONTEMPORÂNEO, PAÍSES EM DESENVOLVIMENTO, BEPS E OUTRAS QUESTÕES ATUAIS - Pereira Valadão, Marcos Aurelio (Revista de Finanças Públicas, Tributação e Desenvolvimento, 2018)
This paper analyzes the Contemporary International Tax System with focus on international tax cooperation, the participants of this context, that goes beyond the countries, and the issues that are present in base erosion and profit shifting (BEPS) Project with the focus on those that are the most important for developing countries, also taking into consideration the Brazilian approach to those issues. It also verifies the role of international organizations (including NGOs), The paper consider other aspects, for example, the south Centre initiative on tax cooperation, and the biased approach from the northern rich countries towards the south poorer economies, coming to the conclusion that the differences between the needs of of developed and developing countries, which affect their tax systems, and the different tax systems itself, must be taken into account.